Promotion Strategy Of Soponyono Restaurant In Maintaining Customer Existence In Kesu' Sub-District, North Toraja District - Jeanne Fransisca Bokko; Mey E.Limbongan (Universitas Kristen Indonesia Toraja, 2022)
Promotion Strategy of Soponyono Restaurant in Maintaining Customer Existence in Kesu' District, North Toraja Regency” This study aims to answer the questions (1) How is the promotion and promotion strategy carried out by Soponyono Restaurant? (2) How to maintain customer existence? This research uses a qualitative descriptive method. Data collection by means of observation, interviews, and documentation with business owners, employees and customers of Soponyono Restaurant. The results obtained from this study are the Promotional Strategy of Soponyono Restaurant using promotional media using social media, namely WhatsApp and YouTube and how to maintain customer existence by being kind, polite and friendly to customers and convincing customers that in Soponyono Restaurant the food and beverage menus are delicious, delicious and comfortable places.